Large bipolar lightning discharge events in winter thunderstorms in Japan. Issue 2 (29th January 2014) - Wu, Ting; Yoshida, Satoru; Ushio, Tomoo; Kawasaki, Zen; Takayanagi, Yuji; Wang, Daohong
Abstract Using a low‐frequency lightning location system comprising nine stations, we have observed and analyzed 374 large and bipolar electric field change waveforms that occurred during the winter of 2012–2013. Since the waveforms are different from those produced by any well‐studied lightning discharge processes, we refer to these source discharge events using a new name: large bipolar events (LBEs). LBEs can be characterized by the following features: (1) All have the same polarity as negative return stroke. (2) All exhibit a single bipolar pulse with a pulse width around 15 µs and similar positive and negative cycles. (3) All are located on the land along the Japan Sea coast, indicating they are probably associated with high grounded objects. (4) Most LBEs produce very large electric field changes that are even larger than that of positive and negative return strokes. (5) Most LBEs are temporally isolated within several milliseconds but are frequently followed by intracloud discharges after tens of milliseconds. (6) Most LBEs produce a single well‐distinguished ionospheric reflection pulse, and the time difference between LBE pulse and the corresponding reflection pulse can be used to calculate ionospheric reflection height. It is speculated that LBE is a type of powerful and transient lightning discharge event produced within a compact region of strong electric field formed when the negative charge layer in thunderclouds is very close to the top of a tall grounded object.